2019
DOI: 10.3390/nu11051017
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry Leaf Polyphenols and Fiber Induce Synergistic Antiobesity and Display a Modulation Effect on Gut Microbiota and Metabolites

Abstract: The antiobesity molecular mechanisms of mulberry leave components were analyzed based on intestinal micro-ecology and metabolomics. An obesity model was established by feeding rats with a high-calorie diet. Rats were divided into seven groups: the obesity model control (MC), positive control (PC), mulberry leaf powder (MLP), mulberry leaf fiber (MLF), mulberry leaf polyphenols (MLPS), mulberry leaf fiber and polyphenols mixture (MLM), and normal control (NC), and fed daily for 6 consecutive weeks. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 40 publications
(43 reference statements)
6
50
3
Order By: Relevance
“…Even the mulberry leaf powder or their extracts have shown antioxidant, antiinflammatory, hypolipidemic, and neuroprotective properties (9,46,47). A substantial decrease in MDA levels in treated groups revealed that MLF possess practical potential to decrease lipid peroxidation, as reported previously in mice model (18,48).…”
Section: Serum Antioxidant Parameterssupporting
confidence: 59%
“…Even the mulberry leaf powder or their extracts have shown antioxidant, antiinflammatory, hypolipidemic, and neuroprotective properties (9,46,47). A substantial decrease in MDA levels in treated groups revealed that MLF possess practical potential to decrease lipid peroxidation, as reported previously in mice model (18,48).…”
Section: Serum Antioxidant Parameterssupporting
confidence: 59%
“…Gut microbiota affects host metabolism by ways of transformation, absorption, and metabolism of exogenous substances (Li et al, 2019). It is rational that the alternation of metabolites reflects the changes of gut microbiota profiles.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the presence of fibers increased the efficiency of polyphenolic extract from mulberry leaf, and the polyphenol-fiber mixture influences the gut microbiota (Table 1). Their synergistic effect resulted in the reduction of Firmicutes abundance, the downstream of Clostridiales and Lachnospiraceae, and a high concentration of butyrate [89]. The effects of synergic polyphenols and dietary fibers has also been described by a study on gastrointestinal digestion of two grape pomace extracts (GPEs) [90].…”
Section: Dietary Fiber and Their Role In The Bioavailability Of Phenomentioning
confidence: 97%